Sejarah Pemikiran Ekonomi Islam : Etika Bisnis Islam pada Masa Rasulullah - Ahmad Wahyudi Zein; Bunga Agustina; Alfatih Faiz Fahlevi; Aly Syibran (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Islam was introduced during the time of the Prophet Muhammad SAW, but only developed significantly in the 1970s. In the sixth and seventh centuries AD, during the life of the Prophet Muhammad SAW and at the same time as the Qur'an was revealed, the concept of Islamic economics began to emerge. Even though Islamic economics is still in the process of development, it has made progress during the reign of the Prophet in Medina, where he succeeded in explaining the principles of financial management. Islamic economic practices during the time of the Prophet, Khulafaurrasyidin, and Tab'in showed how important the market was. The Prophet highly appreciated reasonable prices determined by market mechanisms.